Academia in crisis : dystopic optimism and postalgic realism in university life - Donskis, Leonidas (Value inquiry book series, 2019)
Academia is standing at a junction in time. Behind lies the community of the curious, ahead the mass and the market. This book joins in a growing stream of works that explore the vicissitudes of present-day European universities in what Bauman coined as liquid times. Here, a number of concerned (engaged) European scholars attempt to defend and brush up academic core values and practices, starting from their own life worlds and positions in higher education. They share the view that there is no point in turning back, nor in mechanically marching straight on. Above all, they uphold that there is no alternative to treasuring academia as a space for thinking together. Hopefully the fruit of this sine qua non invites to think with, and envision academic activism. Contributors are Samuel Abraham, Stefano Bianchini, Simon Charlesworth, Leonidas Donskis, Frans Kamsteeg, Joost van Loon, Ida Sabelis, Tamara Shefer and Harry Wels.